2015
DOI: 10.1111/ejed.12142
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Research Productivity in Spanish Academia

Abstract: This article aims to widen the empirical evidence about the determinants of Spanish academics’ publication productivity across fields of study. We use the Spanish Survey on Human Resources in Science and Technology addressed to Spanish resident PhDs employed in Spanish universities as academics. Productivity is measured as the total number of publications in a three‐year period. We show how personal and academic variables explain differences in productivity within universities and fields of studies and across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 27 publications
4
40
0
Order By: Relevance
“…For every additional hour of research assistance per week, faculty productivity increased by .140 publications per year. This result is consistent with Dundar and Lewis (1998) who found that employing more graduate students as research assistants had a positive impact on faculty research productivity across all fields within the university.…”
Section: Factors Affecting Quantity Of Publicationssupporting
confidence: 90%
See 3 more Smart Citations
“…For every additional hour of research assistance per week, faculty productivity increased by .140 publications per year. This result is consistent with Dundar and Lewis (1998) who found that employing more graduate students as research assistants had a positive impact on faculty research productivity across all fields within the university.…”
Section: Factors Affecting Quantity Of Publicationssupporting
confidence: 90%
“…From an institutional standpoint, a variable such as the size of the faculty in the department, which would be indicative of the individual's potential for direct collaboration, may have been significant in the present study (Dundar and Lewis, 1998). However, from a pragmatic standpoint, it would be impossible for any study to capture all the potential determinants of (Lee and Bozeman, 2005) or individual motivation (Bland, Center, Finstad, Risbey, & Staples, 2005).…”
Section: Limitations and Future Studiesmentioning
confidence: 93%
See 2 more Smart Citations
“…The difference between female and male economists in research productivity and career advancement has been documented in a number of studies (see, e.g., Albert et al, 2016;Ginther and Hayes, 2003;Ginther and Kahn, 2004;Kahn, 1993;Maske et al, 2002). Contributing to the existing literature, in this section, we aim to examine the extent to which the benefit of conference presentation on publishing for female authors is different from that for male…”
Section: Gender Effectmentioning
confidence: 99%